PENGEMBANGAN MEDIA PEMBELAJARAN VIDEO MENGGUNAKAN APLIKASI POWTOON PADA MATERI KARAKTERISTIK TRANSISTOR - Kusumastuti, Alita; Partono, Partono; Alarifin, Dedy Hidayatullah; Harjati, Purwiro (Universitas Muhammadiyah Metro, 2022)
Abstract: The product developed is a video learning media using a powtoon application on transistor characteristics. The development of this learning media is needed to assist teaching and learning activities during the pandemic, both online and offline learning. Online learning or non-face-to-face learning requires learning media that are easy to access and use. The purpose of research and development of this learning media is to produce a product in the form of ICT-based audiovisual learning media, namely video learning media using a powtoon application on transistor characteristics.This type of research uses the ADDIE development method. This method consists of 5 stages, namely Analysis, Design, Development, Implementation, Evaluation. The instrument used is an assessment questionnaire. There are two methods used: the first is an expert validation questionnaire with 2 assessments (material and media), this validation is used to assess the feasibility of the media, and the second is a student response questionnaire to assess the user's response to the developed media.Based on the results of the validation with the results of the percentage value of the feasibility of the tool, namely 93.35% for media experts with very feasible criteria, 92.7% for material expert validation with very feasible criteria and 75.78% for student responses with appropriate criteria. From the results of these data obtained an average percentage of 87.28% with proper criteria. Based on the exposure of the results of the product feasibility test and the practicality of the product, it can be concluded that the video learning media using the Powtoon application on transistor characteristics, teaching materials for integers and fractions with Islamic values is very feasible and practical to use for learning.Keywords: learning media; powderoon; transition; development